Quantum Chemistry in Historical Perspective - Kampouridis, S.; Simões, A.; Arabatzis, T. (O. Lombardi et al (eds.), Philosophical Perspectives in Quantum Chemistry, 2022)
Quantum chemistry is a firmly established branch within theoretical chemistry. However, in the late 1920s and early 1930s when the first foundational papers and books appeared, mostly written by physicists as well as by chemists or chemical physicists, the disciplinary identity of the emerging field was a contentious issue: Was it physics or was it chemistry? This question was tied to the problem of reductionism and received different answers, which led to different ways of practicing quantum chemistry and eventually stabilized its identity as an in-between/ boundary discipline. During its subsequent development the question of disciplinary identity continued to be central, as quantum chemistry established connections to other disciplines and was deeply shaped by computing technology. In this chapter we discuss the historical development of quantum chemistry, integrating several strands, conceptual, institutional, methodological, and epistemological.